Morphology of the dentin on primary molars after the application of phosphoric acid under different conditions - Pimenta,Renata Antonini (2010)
The aim of this study was to evaluate changes in the superficial dentin pattern of primary teeth after applying different phosphoric acid concentrations and conditioning times. Twenty-four dentin surfaces were divided in 4 groups with 10 teeth each: GI -no treatment; GII to GIV -phosphoric acid at 37%, 32%, and 10% respectively. The samples were divided into two halves: one treated for 7 seconds (T1) and the other one for 15 seconds (T2). They were submitted to scanning electronic microscopy (SEM). A reticule was superimposed upon the images to randomly select dentinal tubules measured in µm². The conditioning times did not cause significant differences in the mean diameter values of the dentin tubules within each test group: GII (T1= 4.86; T2= 4.70); GIII (T1 = 3.83; T2= 3.08); GIV (T1= 5.04; T2= 5.23). Comparing different groups, there were no differences in T1. The same results were observed in T2, except for GIV which presented higher mean diameter values than GIII. The extent of acid conditioning did not influence tubule opening within groups. When different types of acids where compared, only the 10% phosphoric acid showed upper tubule opening than 32% phosphoric acid. The dentin pattern varied according to the type of acid used for conditioning.